Factors influencing HIV positive individuals attending anti-retroviral therapy (ARV) clinic at Katutura Hospital (Windhoek, Namibia) to disclose or not to disclose their HIV status to their sexual partners - Samatanga, Fortune (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.